2020
DOI: 10.1021/acsami.0c08716
|View full text |Cite
|
Sign up to set email alerts
|

Full Poly(ethylene glycol) Hydrogels with High Ductility and Self-Recoverability

Abstract: Energy dissipation is a common mechanism to improve the ductility of polymeric hydrogels. However, for poly­(ethylene glycol) (PEG) hydrogels, it is not easy to dissipate energy, as polymer chains are dispersed in water without strong interchain interactions or decent entanglement. The brittleness limits the real applications of PEG hydrogels, although they are promising candidates in biomedical fields, as PEG has been approved by the U.S. Food and Drug Administration. Herein, we chemically introduced a center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…This novel mechanism enables efficient polymerization of high-molecular-weight diols with dicarboxylic acids, which is unable to be achieved by the traditional direct polyesterification method. 47 Following a two-step process, PEGs were first esterified with excess MSA (1.5 equiv) to form a carboxyl-terminated prepolymer; then, the molecular chains were continuously propagated by regenerating MSA and subliming it from the polymerization system under a reduced pressure (<100 Pa). Despite strong hydrophilicity of PEG, we found that the polymerization of the two PEGs with MSA significantly influences the aqueous solubility of the polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel mechanism enables efficient polymerization of high-molecular-weight diols with dicarboxylic acids, which is unable to be achieved by the traditional direct polyesterification method. 47 Following a two-step process, PEGs were first esterified with excess MSA (1.5 equiv) to form a carboxyl-terminated prepolymer; then, the molecular chains were continuously propagated by regenerating MSA and subliming it from the polymerization system under a reduced pressure (<100 Pa). Despite strong hydrophilicity of PEG, we found that the polymerization of the two PEGs with MSA significantly influences the aqueous solubility of the polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Here, we prepared a full-PEG micellar nanodrug with reduction-responsive properties based on an amphiphilic PEG derivative (Figure a), which was synthesized from copolymerization of two PEGs with different molecular weights (i.e., PEG 200 and PEG 10k ) and mercaptosuccinic acid (MSA) via a previously reported carboxyl-ester transesterification (CET) mechanism. , This amphiphilic PEG derivative can spontaneously form micelles with a core–shell structure in the aqueous environment via self-assembly (Figure b). Paclitaxel (PTX) is thereby encapsulated into the micellar core by taking advantage of the hydrophobic interaction between PTX and the hydrophobic segment of the PEG derivative.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to disperse energy in PEG hydrogels. Ge et al [ 129 ] investigated solutions to this limitation. In the presence of succinic acid and mercaptosuccinic acid as dicarboxylic acids, PEG derivatives were designed via melt polycondensation of triethylene glycol (PEG (150)) and high-molecular-weight PEG.…”
Section: Polymer Materials For Ammentioning
confidence: 99%
“…Figure 2 shows the variety of micro-/nanoparticles and hydrogels according to their diverse properties. covery of hydrogel [37]. Microparticles are found to make up for the deficiency of hydrogel in mechanical and stable properties.…”
Section: The Preparation and Main Properties Of The Micro-/nanoparticle Hybrid Hydrogel Platformmentioning
confidence: 99%
“…A great number of researchers have already focused on this for research into multi-field as well as cartilage-related diseases. Some studies show that nanospheres can enhance lubrication [36], ductility, and self-recovery of hydrogel [37]. Microparticles are found to make up for the deficiency of hydrogel in mechanical and stable properties.…”
Section: Introductionmentioning
confidence: 99%